Impact of Quizizz Learning Media in Increasing Interest and Motivation for Learning in Early Childhood Education Students - Aini, Siti Noor; Ardah, Fenni Kurniawati; Mahendika, Devin; Guilin, Xie; Amir, Hasbiyah Srianah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Along with the times of technology in the field of education, there are many updates in the use of learning media, one example is by using the Quizizz application. The Quizizz application really helps teachers in the teaching and learning process. The Quizizz application has many interesting features, and makes learning more fun. This quizizz application is one of the learning media chosen by teachers to carry out the learning process in early childhood. The purpose of this study was to determine how much impact quizizz learning media has on increasing early childhood learning interest and motivation. This study uses a skinative method in which the data is obtained through the introduction of the quizizz application to early childhood and direct interviews with several parties such as teachers and parents of children. The results showed that the use of the Quizizz application in early childhood was carried out well starting from the planning, implementation, and evaluation stages. From this research it can be concluded that this quizizz application is very helpful in the learning process of children so that children more quickly understand the lessons conveyed by the teacher and with interesting features can also make children's learning motivation increase. The limitation of this research is that researchers only conduct research on early childhood quizizz applications even though there are still many applications that can be used to provide learning motivation in early childhood. Researchers hope that future researchers can conduct research related to early childhood learning motivation but using other learning media. This study recommends that future researchers make research as a reference in conducting research on the impact of quizizz applications in increasing early childhood learning motivation.